2021
DOI: 10.1002/qj.4011
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of convective characteristics during tropical cyclogenesis

Abstract: Four idealized, high-resolution (500 m horizontal grid spacing), numerical simulations are used to investigate the evolution of convective structures during tropical cyclogenesis. The simulations all begin with a weak initial axisymmetric cloud-free vortex in a quiescent environment, but differ in the moisture level of the initial sounding and whether or not ice microphysical processes are considered. Irrespective of experimental setup, there is only a short period where shallow or congestus clouds dominate. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Although the absolute mass flux of shallow convective clouds with maximum MFH below 2 km is small (See Figure S1), they occur most frequently over the domain. Some studies showed that the shallow cumulus convection plays an important role in TC formation (Wang, 2014) and intensification (Kilroy, 2021). Due to the high frequency of occurrence, the parameterization for shallow convective clouds should be paid more attentions.…”
Section: Composite Analysis By Maximum Mass Flux Heightmentioning
confidence: 99%
“…Although the absolute mass flux of shallow convective clouds with maximum MFH below 2 km is small (See Figure S1), they occur most frequently over the domain. Some studies showed that the shallow cumulus convection plays an important role in TC formation (Wang, 2014) and intensification (Kilroy, 2021). Due to the high frequency of occurrence, the parameterization for shallow convective clouds should be paid more attentions.…”
Section: Composite Analysis By Maximum Mass Flux Heightmentioning
confidence: 99%
“…Rotation of sub‐severe storms—those not meeting National Weather Service severe weather criteria—has apparently not been studied at all. VHTs are beginning to be observed through geostationary satellites and in some aircraft observations (Hogsett & Stewart, 2014) but most effort at understanding these uses regional simulations, and exclusively in the context of mature and intensifying tropical cyclones where there has been some effort to better understand their role in genesis and intensification (Kilroy, 2021, and references therein; Wang, 2018; Zawislak, 2020, and references therein; Hendricks et al., 2004). An appreciation for rotating updrafts elsewhere is virtually absent.…”
Section: Introductionmentioning
confidence: 99%